Russian-Ukraine 2022 War: A Review of the Economic Impact of Russian-Ukraine Crisis on the USA, UK, Canada, and Europe - Mbah, Ruth Endam; Wasum, Divine (Advances in Social Sciences Research Journal, 2022)
The popular belief worldwide is that the global financial sanctions unleashed on Russia, the seizure of assets and properties of the oligarch friends to President Putin for Russia’s current attack on Ukraine will cripple the Russian economy and hinder any further attack on Ukraine. This is logical reasoning, however, the impact of this crisis extends to the global economy. Thus, the purpose of this study is to review the economic impact of the 2022 Russia-Ukraine war on key global economic actors, specifically, countries that have unleashed financial sanctions on Russia as punishment like the USA, Canada, UK, and EU. This study uses the Social Contract and the Interest Group Theories to explain the rationale behind this crisis from its origin. Evidence from reviewed literature shows that although the consequences of this crisis have had a fatal impact on Russia’s economy, the world economy has begun to feel the impact of this crisis. Inflation which is already ravaging most global economies is steadily rising due to the sharp increase in oil, natural gas, and food prices just a few days into this crisis. Experts expect a negative impact on household consumption, increase uncertainty, unpredictable stock swings, supply chain disruptions, bulging utility bills, decreased investment due to political risks, and economic growth impediments. It is therefore vital for policymakers worldwide to seek alternative means of survival if Russia decides to react by restricting its export of vital global commodities of which it is a significant export leader like oil, natural gas, wheat, neon, titanium, palladium, and ammonium nitrate.